2017
DOI: 10.1002/chem.201700360
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Interconversion of a Dinuclear Au Species Supported by a Redox‐Active Bridging PNP Ligand Facilitates Ligand‐to‐Gold Electron Transfer

Abstract: Redox non‐innocent ligands have recently emerged as interesting tools to obtain new reactivity with a wide variety of metals. However, gold has almost been neglected in this respect. Here, we report mechanistic investigations related to a rare example of ligand‐based redox chemistry in the coordination sphere of gold. The dinuclear metal‐centered mixed‐valent AuI–AuIII complex 1, supported by monoanionic diarylamido‐diphosphine ligand PNPPr and with three chlorido ligands overall, undergoes a complex series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…This ligand and its close relatives support a tremendous wealth of coordination chemistry, with tridentate pincer binding modes observed across the periodic table For coinage metals, however, PNP ligands often favor dinuclear coordination modes with bridging amides, such that each metal is only bound in a bidentate fashion . The first PNP gold complexes, recently reported by van der Vlugt and co‐workers, are structurally and electronically intriguing dinuclear gold systems that do not adopt pincer binding modes , …”
Section: Introductionmentioning
confidence: 91%
“…This ligand and its close relatives support a tremendous wealth of coordination chemistry, with tridentate pincer binding modes observed across the periodic table For coinage metals, however, PNP ligands often favor dinuclear coordination modes with bridging amides, such that each metal is only bound in a bidentate fashion . The first PNP gold complexes, recently reported by van der Vlugt and co‐workers, are structurally and electronically intriguing dinuclear gold systems that do not adopt pincer binding modes , …”
Section: Introductionmentioning
confidence: 91%
“…The second reaction shown in Scheme , the reaction of the mixed gold(I)‐gold(III) complex 21 with silver triflimide, most likely involves radical intermediates as well, but actually does not produce a pincer complex. The unusual synthesis of the previously reported Cbz ( R PNP)H protioligand via oxidative coupling of two aryl rings represents a hitherto unique synthetic pathway to a complex such as the gold(I)‐gold(I) compound 22 , . For Pyr ( Ph PNP)H, similar dinuclear copper and silver complexes with protonated pyrrole rings have been prepared, either starting from the protioligand and different cuprous halides or from Pyr ( Ph PNP)‐coordinated nickel complexes via metal exchange with different silver salts …”
Section: Preparation Of Pnp Pincer Complexesmentioning
confidence: 99%
“…Previous studies have reported that PNP ligands and carbanionic ligands alter the redox properties of gold. 59 , 60 In addition, ligands could facilitate the internalization of AuNPs at the cellular level, which may occur through the endocytosis process. 61 Although ligands help stabilize nanoparticles during their synthesis and facilitate their internalization, their presence in cells mainly affects the catalytic activity of their substrate.…”
Section: Introductionmentioning
confidence: 99%